2020
DOI: 10.1111/1346-8138.15534
|View full text |Cite
|
Sign up to set email alerts
|

Expression of discoidin domain receptor 1 and E‐cadherin in epidermis affects melanocyte behavior in rhododendrol‐induced leukoderma mouse model

Abstract: Vitiligo is a depigmentation disease characterized by gradual loss of melanin and melanocytes from the epidermis. The mechanism of melanocyte loss is not yet known. In this report, we showed that the expression of discoidin domain receptor 1 and E‐cadherin, known adhesion molecules, was variable or absent in the epidermis of rhododendrol‐induced leukoderma (RDIL) mice during the depigmentation process. Our findings suggest that melanocyte damage by rhododendrol promotes reduction of adhesion molecules not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In the present report, skin pigmentation accompanied with an increase in the number of epidermal melanocytes surprisingly occurred in skin irradiated with a lower dose of MEL in RD-treated guinea pigs, when compared with control animals. It was reported that the application of RD-induced melanocyte cell death and temporarily reduced the expressions of E-cadherin and DDR1, inducing melanocyte floating in a tyrosinase-dependent manner in mice [ 45 , 46 ]. In our previous report, the number of DOPA-positive melanocytes was greatly reduced by applying RD to guinea pigs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, skin pigmentation accompanied with an increase in the number of epidermal melanocytes surprisingly occurred in skin irradiated with a lower dose of MEL in RD-treated guinea pigs, when compared with control animals. It was reported that the application of RD-induced melanocyte cell death and temporarily reduced the expressions of E-cadherin and DDR1, inducing melanocyte floating in a tyrosinase-dependent manner in mice [ 45 , 46 ]. In our previous report, the number of DOPA-positive melanocytes was greatly reduced by applying RD to guinea pigs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discoidin domain receptor 1 (DDR1) forms complexes with E-cadherin [77] and acts as a collagen IV adhesion receptor, thereby regulating the location of melanocytes at the basement membrane zone [78]. As genetic variants of the DDR1 gene are observed in Brazilian [79] and Korean [80] populations, dysfunction of DDR1 may be associated with vitiligo pathogenesis, although further functional analysis is necessary [81]. Bastonini et al also summarizes the involvement of keratinocytes, fibroblasts, and the extracellular matrix in vitiligo pathogenesis [82].…”
Section: Pathogenesis Of Vitiligomentioning
confidence: 99%
“…54,55 Both E-cadherin and DDR1 expression in keratinocytes resumed after disappearance of damaged melanocytes from the epidermis. 56 The weaker expression of E-cadherin and DDR1 adhering melanocytes to the epidermis basal layer has been implicated as one of the aggravating factors in the loss of melanocytes in vitiligo. It is quite possible that injured melanocytes affect the surrounding keratinocytes, subsequently altering the adhesion molecules.…”
Section: Epithelial Cadherin and Discoidin Domain Receptor Tyrosine K...mentioning
confidence: 99%